2015
DOI: 10.1371/journal.pone.0126027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tangshen Formula on Patients with Type 2 Diabetic Kidney Disease: A Multicenter Double-Blinded Randomized Placebo-Controlled Trial

Abstract: BackgroundPersons with diabetes are at high risk of developing diabetic kidney disease (DKD), which is associated with high morbidity and mortality. Current drug therapies for DKD, such as angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), are not entirely satisfactory. This study aimed to evaluate the additional benefit and safety of the Chinese herbal granule Tangshen Formula (TSF) in treating DKD.MethodsThe study was designed as a six-center randomized, double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 45 publications
4
106
0
Order By: Relevance
“…Multiple clinical studies by Ping Li’s research group have demonstrated the efficacy of the Tangshen formula in attenuating diabetic kidney disease in rodent models and human patients [25]. Notably, a 2015 multicenter RCT in type 2 diabetic patients with diabetic kidney disease has also revealed that the Tangshen formula produces a significant decrease in 24-hour urinary protein as well as significant improvements in the estimated glomerular filtration rate (eGFR) relative to placebo [26]. In addition, our finding regarding the efficacy of ramipril ACEI monotherapy in type 2 diabetes patients with microalbuminuria concords with a previous network meta-analysis by Vejakama et al, which demonstrated a superior reno-protective effect with ACEI monotherapy or ARB monotherapy over CCB monotherapy or placebo in type 2 diabetic patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies by Ping Li’s research group have demonstrated the efficacy of the Tangshen formula in attenuating diabetic kidney disease in rodent models and human patients [25]. Notably, a 2015 multicenter RCT in type 2 diabetic patients with diabetic kidney disease has also revealed that the Tangshen formula produces a significant decrease in 24-hour urinary protein as well as significant improvements in the estimated glomerular filtration rate (eGFR) relative to placebo [26]. In addition, our finding regarding the efficacy of ramipril ACEI monotherapy in type 2 diabetes patients with microalbuminuria concords with a previous network meta-analysis by Vejakama et al, which demonstrated a superior reno-protective effect with ACEI monotherapy or ARB monotherapy over CCB monotherapy or placebo in type 2 diabetic patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…The db/m mice were used as controls (n=9, db/m). The TSF dosage was based on our previous study and standard conversion formula (body surface areas) (15,16). Body weight was measured weekly (g).…”
Section: Methodsmentioning
confidence: 99%
“…In short, counting on the undiagnosed patients who do not yet realize their condition, the overall prevalence of DN is unoptimistic. Particularly, Table 1 summarizes selected studies that evaluated DN incidences and outcomes in diabetic nephropathy patients and also are related to the topic [1016]. American Diabetes Association accurately defined diabetes mellitus as “a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both” [17].…”
Section: The Epidemiology Of Dnmentioning
confidence: 99%
“…Historically, conventional medicines, such as ACEI or ARB, are not able to totally prevent the development of DN [16]. Thus, there is an urgent need to find new effective agents to delay the progression of DN.…”
Section: The Future Therapies Of Dnmentioning
confidence: 99%